Perencanaan dan Penganggaran pada IAIN Madura dalam Kerangka Keuangan Negara - Fakhrurraji, Ahmad (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This article describes planning and budgeting as a small part of the cycle of state financial management in Indonesia. IAIN Madura as a government agency and part of the State Islamic Religious College (PTKIN) under the Ministry of Religion of the Republic of Indonesia continuously strives to improve the quality of state financial management amid the dynamics of the nation's economy through the planning and budgeting process. The purpose of this study is to determine the stages of planning and budgeting at IAIN Madura and to analyze it from the point of view of state finances. The research method uses a descriptive qualitative approach. Data collection through observation and in-depth interviews with interested parties. The data used are planning and budgeting documents in the form of strategic plan documents, work plans, and DIPA, RKA-K/L. The results showed that IAIN Madura in the process of planning and budgeting had followed the rules and regulations that were in force.